Analisis Penerapan Strategi Segmenting, Targeting, dan Positioning dalam Memasarkan Kredit Pemilikan Rumah - Panca Sagita, Leni Anggraeni; Huda, Badriyatul (Jurnal Dimamu, 2024)
Based on the results of observations, the background to this research is the fluctuation in the number of KPR credit customers caused by strategic planning and strategy implementation carried out by Bank BJB Jatinangor Branch Office. This research aims to find out how to implement the Segmenting strategy, Targeting and Positioning in marketing home ownership loans at Bank BJB Jatinangor Branch Office. The object of this research is the marketing strategy in marketing home ownership loans at Bank BJB Jatinangor Branch Office. The type of research used is qualitative with a descriptive approach. The type of data is primary data with data collection techniques of observation, interviews, literature study and documentation. The research results show that (1) there are four indicators that constitute a segmenting strategy, namely demographics, behavior, psychographics and geography. (2) there are two indicators that become targeting strategies, namely selective specialization and product specialization strategies. (3) there are four indicators that become a positioning strategy, namely attributes, price, product users, and benefits. The data analysis technique used in this research is the interaction analysis technique model, namely a process carried out through four stages, namely data collection, data reduction, data presentation and conclusions. The object of this research is an analysis of the application of segmenting targeting and positioning strategies in marketing home ownership credit (KPR) at Bank BJB Jatinangor branch office.